Berpikir Kritis Siswa dalam Menyelesaikan Masalah Matematika Kontekstual Terbuka Ditinjau dari Gaya Kognitif Reflektif dan Impulsif - Sari, Silvia Novita; Rosyidi, Abdul Haris (MATHEdunesa, 2025)
Critical thinking is one of the skills needed to solve problems. Cognitive style has an important role in developing critical thinking skills. This study aims to describe students' critical thinking in solving open contextual math problems based on reflective and impulsive cognitive styles. This research is a qualitative descriptive. The subjects in this study consisted of two students of VIII grade at junior high school in Surabaya who had reflective and impulsive cognitive styles. The instruments in this study were Matching Familiar Figure Test (MFFT), critical thinking test of contextual open-ended problems, and interview guidelines. The data of this study were analyzed based on critical thinking indicators adapted from Jacob & Sam's critical thinking indicators. The results showed that in general students with reflective and impulsive cognitive styles went through four stages of critical thinking namely clarification, assessment, inference, and strategy. Students with reflective cognitive style solve problems with clear and detailed steps and arguments, and the time required tends to be long. At the strategy stage, students are able to determine other different alternative solutions. Meanwhile, students with impulsive cognitive style solve problems with steps and arguments that are short and the time required tends to be fast. At the strategy stage, students tried to determine other different alternative solutions even though in the end they could not find them.